DAMPAK DANA DESA TERHADAP TINGKAT PEREKONOMIAN MASYAKARAT DI DESA TANJUNG BUGIS - Ahmad Yasir (Cross-border, 2019)
This study aims to determine the results of the implementation of development activities from village funds, the impact of village funds on the community economy from infrastructure development programs, improving the quality of human resources (both formal and non-formal education) on the level of community income. This research was conducted in the village of Tanjung Bugis which has 3 hamlets and 12 RTs, the number of respondents in the study was 100 respondents with a sample distribution according to the number of 12 RTs in 3 hamlets plus 10 village officials. The data analysis technique used in this research is qualitative descriptive analysis, using data collection methods that can be obtained directly from respondents by filling out questionnaires, in-depth interviews, making observations and from discussions. The results showed that the infrastructure and human resources development program that had been planned, the achievement of physical development in the last 3 years had reached 80% of the target and the achievement of human resource development had been realized by 45% of the target. There has been an increase in the welfare of the community as a result of the infrastructure development program and the improvement of human resources through skills training to improve the welfare of the community.